A systematic approach to reduce cultural bias: An illustration from the adaptation of the Addenbrooke's Cognitive Examination III for the Bengali speaking population in India. (20th December 2022) - Dutt, Aparna; Nandi, Ranita; Rao, P.Sulakshana; Bhargava, Pallavi; Gopalkrishnan, Subha; Bose, Arpita; Ghosh, Amitabha; Evans, Jonathan J.
Abstract: Background: A systematic approach is vital for adapting neuropsychological tests developed and validated in the western, educated and English populations. However, rigorous and uniform methods are often not implemented during adaptation of neuropsychological tests and cognitive screening tools across different languages and cultures. This has serious clinical implications. The naming test from the Addenbrooke's Cognitive Examination (ACE) III will be presented as an example to illustrate a systematic approach for selecting culturally appropriate and psychometrically reliable items for a literate Bengali speaking population in India. Method: Two studies were conducted in seven phases for adapting the ACE III naming test. Twenty‐three items from the naming test in the English and the different Indian ACE‐R versions were administered to healthy Bengali speaking literate adults for determining image agreement, naming and familiarity of the items. Eleven items were identified as outliers. We then included 16 culturally appropriate items that were semantically close to the items in the selected ACE‐R versions of which 3 were identified as outliers. The final corpus consisting of 24 items was administered to 30 patients with mild cognitive Impairment, Alzheimer's disease and vascular dementia, and 60 healthy controls matched for age and education to determine which items in the corpus best discriminated patients and the controls, and also their difficulty levels. Result: The ACE III Bengali naming test with an internal consistency of .87 included 12 psychometrically reliable, culturally relevant high naming‐high familiarity and high naming‐low familiarity living and non‐living items. Item difficulty ranged from .47 to .88 and had discrimination indices ≥.44. Conclusion: A systematic approach helps to determine whether a test is appropriate for the cultural context (within nations also) in which it is intended to be used, and also the possible reasons if inappropriate, which subsequently determines the principle/framework for test adaptation. Adaptation of neuropsychological tests based on familiarity driven approach helps to reduce cultural bias at the content level. This coupled with appropriate item selection statistics helps to improve the validity of the adapted tests and ensure cross‐cultural comparability of test scores both across and within nations.